The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/ird.2299
|View full text |Cite
|
Sign up to set email alerts
|

Variable Rate Precision Irrigation Technology for Deficit Irrigation of Processing Tomato

Abstract: Centre pivot machines, with a variable rate irrigation (VRI) package that provides individual sprinkler control systems (VRI iS), are not common. This research focuses on how uniform the water distribution is under VRI control, and on the size of over‐ and under‐irrigated areas and volumes. Moreover, we wanted to know how wide transition zones are. We conducted different uniformity measurements using common rain gauges for measuring water application depths. Besides grid shape and radial direction measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Given this depletion rate, scientists have predicted that 35% of the Southern High Plains will not be able to support irrigation in 30 years. Many other water resources in the world are depleting rapidly in recent years with negligible recharge, indicating the need for water conservation solutions in agriculture [4,5]. More effective and efficient management of water is required to better conserve water and improve water use efficiency for sustainable crop production.…”
Section: Introductionmentioning
confidence: 99%
“…Given this depletion rate, scientists have predicted that 35% of the Southern High Plains will not be able to support irrigation in 30 years. Many other water resources in the world are depleting rapidly in recent years with negligible recharge, indicating the need for water conservation solutions in agriculture [4,5]. More effective and efficient management of water is required to better conserve water and improve water use efficiency for sustainable crop production.…”
Section: Introductionmentioning
confidence: 99%
“…Since the irrigation system was newly installed, the water distribution and transition between zones were evaluated. The results were published in a previous study [30]. The results showed that another treatment could be added to the experiment, so the I75 (75% of I100) was set in 2018 and 2019, modifying the size of treatment plots to 25 m × 50 m. K plots were irrigated only at fertilisation events to wash the granulates off the leaves, thus avoid scorching (26, 28.8, and 22.6 mm irrigation water above precipitation was applied in 2017, 2018, and 2019, respectively).…”
Section: Irrigation System Methods and Treatmentsmentioning
confidence: 86%
“…Deficit irrigation is commonly used as an irrigation water-saving strategy in the practice of processing tomato production [30]. Water use efficiency increases due to mild and moderate water stress [38], and this method also contributes to the reduction of irrigation costs [39].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several worthwhile investigations on the uniformity and precision of centre pivot VRI systems have been carried out. Sui and Fisher (2015), Takács et al (2018), Clark et al (2003) and Dukes and Perry (2006) evaluated the Heermann and Hein uniformity coefficient (CUH), Christiansen uniformity coefficient (CUc%) and distribution uniformity coefficient (DU%).…”
Section: Introductionmentioning
confidence: 99%